Widely Targeted Metabolomics Analysis of the Changes to Key Non-volatile Taste Components in Stropharia rugosoannulata Under Different Drying Methods - Liu, Yi; Meng, Fangbo; Tang, Pengyu; Huang, Daomei; Li, Qixing; Lin, Mao (Frontiers in Nutrition, 2022)
Stropharia rugosoannulata is an extremely perishable edible fungi product; however, drying can delay its deterioration. Currently, which drying method is the most suitable for the drying of S. rugosoannulata remains unknown, and we have limited comprehensive knowledge of the changed non-volatile taste metabolites as caused by drying processes. Here, an LC-MS/MS-based widely targeted metabolome analysis was conducted to investigate the transformation mechanism of S. rugosoannulata non-volatile taste components after undergoing hot air drying (HAD), vacuum freeze drying (VFD), and microwave vacuum drying (MVD). A total of 826 metabolites were identified, 89 of which—48 amino acids, 25 nucleotides, 8 organic acids, and 8 carbohydrates—were related to non-volatile taste. The drying method used and the parts of S. rugosoannulata (stipe and pileus) influenced the differences found in these metabolites. The possible mechanisms responsible for such chemical alterations by different drying methods were also investigated by a KEGG pathway analysis. Amino acid metabolism (alanine, aspartate, and glutamate metabolism; glycine, serine, and threonine metabolism; arginine and proline metabolism; valine, leucine, and isoleucine biosynthesis) was the main metabolic pathway involved. Pathway enrichment analysis also identified differences in non-volatile taste components among three drying methods that may be closely related to the applied drying temperature. Altogether, the results indicated that as an economical and convenient drying method, HAD is conducive to improving the flavor of S. rugosoannulata and thus it harbors promising potential for practical applications.